2021
DOI: 10.1111/ner.13380
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness in the Right Anterior Cingulate Cortex Relates to Clinical Response to Left Prefrontal Accelerated Intermittent Theta Burst Stimulation: An Exploratory Study

Abstract: Objectives: Accelerated intermittent theta burst stimulation (aiTBS) is a promising treatment option for depressed patients. However, there is a large interindividual variability in clinical effectiveness and individual biomarkers to guide treatment outcome are needed.Materials and Methods: Here, the relation between cortical thickness and clinical response (17-item Hamilton Depression Rating Scale) was studied using anatomical MRI data of 50 depressed patients who were included in a randomized, sham-controlle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 48 publications
1
13
0
Order By: Relevance
“…We did not find a statistically significant link between cortical thickness and treatment response. The link between cortical thickness and the responses to ECT ( 62 ), tDCS ( 63 ), and rTMS ( 17 , 18 ) has been reported before. Boes et al ( 18 ) describe that cortical thickness in the left rostral anterior cingulate cortex region correlates with rTMS treatment response in 48 TRD patients treated with HF (10 Hz) rTMS over the left DLPFC baseline.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…We did not find a statistically significant link between cortical thickness and treatment response. The link between cortical thickness and the responses to ECT ( 62 ), tDCS ( 63 ), and rTMS ( 17 , 18 ) has been reported before. Boes et al ( 18 ) describe that cortical thickness in the left rostral anterior cingulate cortex region correlates with rTMS treatment response in 48 TRD patients treated with HF (10 Hz) rTMS over the left DLPFC baseline.…”
Section: Discussionsupporting
confidence: 56%
“…In fact, patients with thinner cortex before treatment tended to have the most clinical improvement. Baeken et al ( 17 ) recently suggested that baseline cortical thickness in the right caudal part of the anterior cingulate cortex was significantly correlated with direct clinical responses in the subgroup that received active aiTBS (21 patients) over the left DLPFC during the first stimulation week, but no correlation was found with delayed response. In this study, we did not confirm the results of these two preceding studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, recent studies have shown that not only the depth of a particular cortical region but also its thickness may influence the outcome of NIBS interventions. As such, the cortical thickness of regions such as the prefrontal (Bulubas et al, 2019; Filmer et al, 2019), cingulate (Baeken et al, 2021; Boes et al, 2018), and motor cortex (Conde et al, 2012) was found to predict the efficacy of NIBS targeting these areas. In addition, it has been reported that cortical thickness of prefrontal and insular regions positively correlates with the measures of resting HRV (Koenig et al, 2021).…”
Section: Discussionmentioning
confidence: 99%